Yeast hydrolysate ameliorates dexamethasone-induced muscle atrophy by suppressing MuRF-1 expression in C2C12 cells and C57BL/6 mice. (March 2022) - Chang, Yeok Boo; Ahn, Yejin; Suh, Hyung Joo; Jo, Kyungae
Graphical abstract: Highlights: Effect of YH on C2C12 cell and DEX-induced muscle atrophy mouse were conducted. YH can promote muscle differentiation in C2C12 cell. YH prevented muscle atrophy via downregulating MuRF-1, FoxO3a, Atrogin-1 in vitro . YH prevented skeletal muscle loss and downregulates MuRF-1 in DEX-induced muscle atrophy mouse model. Abstract: In this study, we evaluated the effects of yeast ( Saccharomyces cerevisiae ) hydrolysate (YH) on muscle differentiation and muscle atrophy inhibitory activity in C2C12 cells and atrophy inhibitory activity in a dexamethasone (DEX)-induced muscle atrophy mouse model. Jenner-Giemsa staining revealed that the length and area of ​​myotubes increased in the YH groups. Moreover, the gene expression of myogenic differentiation 1 and myogenin was significantly increased in the YH groups. In the DEX-induced muscle atrophy C2C12 model, the expression of muscle ring-finger protein-1 (MuRF-1), forkhead box class O3a, and Atrogin-1 were significantly reduced in the YH groups. Furthermore, in the muscle-atrophy mice model, grip strength and lean mass were increased by 1.28-fold and 3.5%, respectively compared to the control in the YH group (300 mg/kg). These results were confirmed by the downregulation of MuRF-1 in muscle. In conclusion, YH promoted muscle cell differentiation and exhibited an inhibitory effect on DEX-induced muscle atrophy.